Development of a simple high-throughput screening protocol based on biosynthetic activity of Mycobacterium tuberculosis glutamine synthetase for the identification of novel inhibitors - Singh, Upasana; Sarkar, Dhiman (Journal of Biomolecular Screening, 2006)
A high-throughput screening protocol has been developed for Mycobacterium tuberculosis glutamine synthetase by quantitative estimation of inorganic phosphate. The K., values determined at pH 6.8 are 22 mM for L-glutamic acid, 0.75 mM for NH4Cl, 3.25 mM for MgCl2, and 2.5 mM for adenosine triphosphate. The K-m value for glutamine is affected significantly by the increase in pH of assay buffer. At the saturating level of the substrate, the enzyme activity at pH 6.8 and 25 degrees C is found to be linear up to 3 h. The reduction of enzyme activity is negligible even in presence of 10% DMSO. The Z' factor and signal-to-noise ratio are found to be 0.75 and 6.18, respectively, when the enzyme is used at 62.5 mu g/ml concentration. The IC50 values obtained at pH 6.8 for both L-methionine S-sulfoximine and DL-phosphothriacin are 500 mu M and 30 pM, respectively, which is lowest compared to the values obtained at other pH levels. The Beckman Coulter high-throughput screening platform was found to take 5 h 9 min to complete the screening of 60 plates. For each assay plate, a replica plate is used to normalize the data. Screening of 1164 natural product fractions/extracts and synthetic molecules from an in-house library was able to identify 12 samples as confirmed hits. Altogether, the validation data from screening of a small set of an in-house library coupled with Z' and signal-to-noise values indicate that the protocol is robust for high-throughput screening of a diverse chemical library.
Keywords: Beckman Coulter; biosynthetic activity; Glutamine synthetase; high-throughput screening; Mycobacterium tuberculosis